Moving sliding mode control for sEMG based prosthetic hand - Taşar, Beyda; Tanyildizi, Alper K.; Gülten, Arif; Yakut, Oğuz (Scientific Publishers of India, 2018)
A prosthetic hand model designed to mimic the motion of a biological hand to take the place of an amputee's real hand. Designed prosthetic hand consist five fingers three joints on each finger. The dynamic behaviour of the prosthetic hand is estimated via SimMechanics. A sliding mode control was applied to the prosthetic hand to track the trajectory as it should be followed for any desired motion pattern without cracking. The performance of the sliding mode controller for three hand patterns of biological hand was tested. © 2018, Scientific Publishers of India. All rights reserved.
Keywords: Electromyography; Prosthetic hand; Sliding mode control; Tract the trajectory; Without cracking